E-KOMPEN (ELEKTRONIK-KOMIK PENDEK) sebagai solusi cerdas dalam meningkatkan minat baca masyarakat Indonesia di era digital - Anwar Efendi Nasution (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2019)
In this journal, the author describes the idea of E-KOMPEN (Short Electronics-Comics) as a smart solution in increasing reading interest in Indonesian society in the digital era. With this solution, it is hoped that it can help the community to increase their reading interest in books, journals, and other sources. Comics are illustrated stories. This idea was motivated by the problem of reading interest in Indonesia. The reading culture in Indonesia is ranked the lowest with a value of 0.001. That is, from around one thousand Indonesian residents, only one has a high reading culture. This condition is much different when compared to America which has an index reading of 0.45 and Singapore 0.55. This solution is expected to be able to answer the challenges of increasing the reading interest of the Indonesian people to improve the quality of Indonesia's human resources. With the increasing quality of Indonesia's human resources, Indonesia's natural resources will be managed well by the Indonesian people themselves without having to make massive imports. Also, Indonesia will be able to use the demographic bonus as well as possible so that the demographic bonus can be a big advantage for Indonesia. Keywords: Comic, reading, library.